Analysis of the efficiency of public expenditure with basic education: a study in the Borborema Potiguar-RN microregion (Research, Society and Development, 2019)
The present study aims to measure the efficiency of the application of public resources in basic education made by Borborema Potiguar-RN municipalities, the study focused on the initial years of Elementary School. The methodology used to calculate the relative efficiency of the 9 municipalities of Borborema Potiguar micro-region was Data Envelopment Analysis (DEA). In this analysis we used secondary data such as per capita student expenditure, number of school census enrollments, average class size per pupil, age-grade distortion rate, Brazilian Proficiency in Mathematics and Portuguese subjects. The data were obtained through the websites of the National Institute of Educational Studies and Research Anísio Teixeira (INEP), National Fund for Educational Development (FNDE), Information System on Public Budgets in Education (SIOPE) and Brazilian Institute of Geography and Statistics (IBGE). The analysis was carried out in the period from 2009 to 2015. The results of the analyzes showed that in 2009, only 22.22% of the municipalities were efficient. In 2010 and 2011 the number of municipalities considered efficient doubled, resulting in a total of 4 municipalities. In the biennium 2012/2013, the percentage of municipalities that were included in the relative efficiency frontier remained the same, as in the last years of the survey, 2014 and 2015. The results of this research help in better decision-making in the educational scope of its managers, in view of necessary checks in those municipalities, in which they are less efficient than others, under the aspect of resource allocation and educational performance